False Narratives: Illicit Practices in Colombian Transnational Adoption - Susan F. Branco; Veronica Cloonan (Genealogy, 2022)
Evidence suggests Colombia’s transnational adoption program maintained systemic problematic practices, some of which were illicit in nature. Examples include child and birthmother trafficking, sale of children, and falsifying or omitting information in adoption documentation. Transnationally adopted Colombian adults encounter significant barriers to accessing their right to know their origins and identity. Despite this, some adult Colombian adoptees are successful in searching for and engaging in birth family reunions. Our study conducted a secondary analysis of an original study on Colombian birth family reunion experiences. We asked the research question, “What discrepancies exist in Colombian transnational adoption narratives?” to perform a directed qualitative content analysis of 17 participant interviews. We found nearly half of our participants reported an illicit practice categorized as child for sale, birthmother trafficking, and abuse of process. Findings underscore the legacy and impact of harmful adoption practices on current adult Colombian transnational adoptees seeking their human right to identity.